2016
DOI: 10.1111/hsc.12335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital engagement on the quality of life of older people

Abstract: What is known about this topic• Some research indicates that older people's use of email and Skype positively affects their quality of life (QOL) by enabling them to keep in touch with friends and relatives.• Research suggests mobile phone ownership can have a positive effect on older people's sense of safety and security. What this paper adds• The empirical evidence demonstrates that the effects of older people's use of ICT, for both mainstream and remote care purposes, on different domains of AbstractIt is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 75 publications
(154 reference statements)
1
95
0
6
Order By: Relevance
“…ICTs can also help to engage people with their communities by encouraging participation and providing access to information and services. This provides control, choice and convenience to rural older people .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICTs can also help to engage people with their communities by encouraging participation and providing access to information and services. This provides control, choice and convenience to rural older people .…”
Section: Discussionmentioning
confidence: 99%
“…Most research on older people's use of ICT has focused on urban areas and examines factors such as prevalence and impact of use, barriers to use and ways to improve engagement . Information and communication technologies influence the lives of urban older people by strengthening social networks and reducing social isolation ; improving cognitive abilities and psychological well‐being ; and providing greater independence and self‐efficacy . While ICT also facilitates access to information and services , those aged over 80 years are more likely to have negative experiences with ICT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown positive correlations between internet use and subjective wellbeing (Choi et al, 2012;Forsman and Nordmyr, 2015;Damant et al, 2016), pointing to the fact that engagement in new technologies might be of importance for successful and active aging.…”
Section: Rational Choice Theories: Technology Acceptance In Later Lifementioning
confidence: 99%
“…Respondents in our study also valued digital communication with our services. However, a recurring theme is service users' concern that implementing technology may be used as an excuse to reduce services, and in particular face to face contact [13], [14] although some studies suggest social benefits [15] .…”
Section: Clearly Health Care Needs To Be Tailored To the Needs Of Indmentioning
confidence: 99%